Anaerobic co-digestion of hydrolysate from anaerobically digested sludge with raw waste activated sludge: Feasibility assessment of a new sewage sludge management strategy in the context of a local wastewater treatment plant. (October 2020) - Zhao, Jiamin; Hou, Tingting; Zhang, Zhenya; Shimizu, Kazuya; Lei, Zhongfang; Lee, Duu-Jong
Highlights: AcoD of anaerobically digested sludge hydrolysate with WAS was examined. The proposed AD + HT170 + AcoD strategy achieved the highest CH4 yield. The new AD + HT + AcoD strategy greatly improved TS reduction and sludge settleability. The AD + HT170 + AcoD strategy can realize much less sludge disposal cost. Engineering and economic feasibility was assessed on the proposed strategy. Abstract: Sustainable sewage sludge management is a worldwide issue in wastewater treatment plants (WWTPs). This work developed a new strategy for sewage sludge treatment involving the integration of hydrothermal treatment (HT) with anaerobic co-digestion (AcoD), particularly on the feasibility of mesophilic AcoD of anaerobically digested sludge (DS) hydrolysate and waste activated sludge (WAS). Results show that AcoD of DS hydrolysate from HT 170℃ for 30 min with WAS achieved the highest CH4 production of 205.39 mL CH4 /g-VSfed . By adopting the new AD-HT170-AcoD strategy, 61.88 mL CH4 /g-tVSfed higher CH4 yield and 22.2% more total solids (TS) reduction were obtained in addition to much better sludge settleability and 7.6% wt. less sludge cake production compared to the conventional mono AD. Although negative energy gain was obtained, the proposed AD-HT170-AcoD strategy is promising, economically feasible, and sustainable when the final sludge disposal of WAS is concerned in the context of whole WWTP.